1678 Impact of anemia in exercise stress echocardiography: effects on exercise capacity and stress testing safety. (17th January 2020) - Bird, J; Morant, K; Kane, G; Mccully, R; Pellikka, P; Luis, S A
Abstract: Funding Acknowledgements: None Background/Purpose: Anemia is a common condition in patients with cardiovascular disease. The effect of anemia in exercise stress testing has not been evaluated in a large cohort of patients. Methods: We performed a retrospective review of patients undergoing exercise stress echocardiography over a 10 year period who had blood hemoglobin assessed within 48 hours of stress testing. World Health Organization cutoffs were used in defining the degree of anemia. The effect of anemia on exercise capacity and stress testing safety outcomes was assessed. Results: In 15, 652 patients, 90.3% were non-anemic, 7.6% mildly anemic, 2.1% moderately anemic, and 0.1% severely anemic. The incidence of serious supraventricular or ventricular arrhythmias and need to transfer to the hospital was low (0.1%) and did not correlate to anemia severity (p = 0.25). There was an increased incidence of non-sustained SVT or atrial fibrillation with moderate anemia and increased incidence of hypotension with stress testing with mild and moderate anemia. There was a significant reduction in duration of exercise (p < 0.001) and METS (p < 0.001) achieved with worsening anemia. Conclusion: Our study demonstrates that exercise stress testing is safe in patients with mild and moderate anemia, albeit with reduced exercise capacity. Low numbers of severely anemic patients despite a large study population limit generalizability of these results in this group.